Emicizumab for All Pediatric Patients with Severe Hemophilia A - Wieland, Ivonne (Hämostaseologie, 2022)
Emicizumab is the first approved nonreplacement therapy for bleeding prophylaxis in hemophilia A (HA) patients. In 2018, it was licensed for HA patients with inhibitors, subsequently followed by an “European Medicines Agency (EMA)” approval for patients with severe HA in the absence of inhibitors in 2019. This is immediately raising the question whether emicizumab is suitable as a first-line treatment for all pediatric patients with severe HA. In this review, we want to discuss what we have, what we know, and what we would like to know. Severe HA is characterized by severe spontaneous and traumatic bleedings, particularly into muscles and joints leading to chronic joint damage. Standard of care is the regular, prophylactic replacement of factor VIII to prevent bleedings. Due to approval of emicizumab—the first nonreplacement therapy for bleeding prophylaxis—in HA patients with inhibitors, and severe HA patients without inhibitors, it is of pivotal interest whether emicizumab could be the first-line treatment in all pediatric patients with severe HA. Clinical trials and real-world observational studies could demonstrate a good efficacy and safety for bleeding prevention during emicizumab treatment in HA patients with and without inhibitors. This clearly indicates that emicizumab could improve HA treatment. However, some crucial and critical questions are remaining with regard to the use of emicizumab. Some of this missing information is already under investigation in the context of clinical trials. Until getting finalized data to shed insights into the points that are currently being discussed, there is a variety of expert and expert group recommendations, which are tackling questions concerning the treatment of HA patients. This review will address major information that is already available, but will also focus on important points that remain to be elucidated in the context of HA treatment.
Keywords: emicizumab; children; PUP; ITI